2014
DOI: 10.1563/aaid-joi-d-11-00224
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Versus Peri-implant Inflammation: Quantification of IL-1β in Partially and Totally Edentulous Patients

Abstract: The aim of this study was to investigate the potential use of salivary IL1β in early-stage diagnostics of peri-implant inflammation in partially and totally edentulous patients rehabilitated with dental implants. Patients were classified according to peri-implant probing depth and bleeding upon probing in groups of healthy individuals or in groups of individuals with peri-implant inflammation. Data on plaque index, clinical attachment loss, suppuration, and mobility were also assessed. Saliva was collected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…These authors suggested that the accuracy of the study results were improved in fully edentulous patients because teeth may influence the results as previously proposed by Liskmann et al [ 30 ]. Rocha et al [ 29 ] observed that healthy edentulous patients present higher levels of nitric oxide than patients with peri-implant inflammation, which corroborated our results. Further research is still needed to confirm our results, since a limitation of this study was the small number of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These authors suggested that the accuracy of the study results were improved in fully edentulous patients because teeth may influence the results as previously proposed by Liskmann et al [ 30 ]. Rocha et al [ 29 ] observed that healthy edentulous patients present higher levels of nitric oxide than patients with peri-implant inflammation, which corroborated our results. Further research is still needed to confirm our results, since a limitation of this study was the small number of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Studies involving nitric oxide analysis in edentulous patients are very scarce. To our knowledge, only one study reported that salivary nitric oxide concentrations are significantly higher in healthy, although fully edentulous, patients in relation to partially edentulous patients with implant-supported overdentures [ 29 ]. These authors suggested that the accuracy of the study results were improved in fully edentulous patients because teeth may influence the results as previously proposed by Liskmann et al [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of all cancers studied, salivary IL-1β has only been measured in oral cancer patients ( Table 1 ). Indeed, several groups have also measured IL-1β from saliva in other noncancer-related pathologies, including peri-implant inflammation in patients with dental implants, 41 periodontitis, 42 , 43 and graft-versus-host disease. 44 This suggests that saliva can be used as a diagnostic tool for detecting early stages of cancer.…”
Section: Saliva: a Model Biological Fluid For Measuring Il-1βmentioning
confidence: 99%
“…Besides microbial markers, salivary IL‐1β levels have been correlated to peri‐implant inflammation and have also been suggested as a potential monitoring tool (Rocha et al. ). Information from multiple biomarkers can be more robust than a single biomarker alone (Gursoy et al.…”
mentioning
confidence: 99%
“…Increased levels of salivary periodontal pathogens have been found in dental implant patients with diseased periodontal status and thus have been proposed as risk indicators for future peri-implant disease (Ito et al 2014). Besides microbial markers, salivary IL-1b levels have been correlated to peri-implant inflammation and have also been suggested as a potential monitoring tool (Rocha et al 2014). Information from multiple biomarkers can be more robust than a single biomarker alone (Gursoy et al 2011;Salminen et al 2014).…”
mentioning
confidence: 99%